PROVISION OF CREDIT FACILITIES TO SUBSIDIARIES BY THE PARENT COMPANY IN VENTURE CAPITAL COMPANIES - Anindhya Nareswari (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
The Governmentin developing and improving companies in BUMN by establishing several stategies, one of which is in the form of a BUMN Holding Company which has a strategy in a corporation, in which companies in the context of BUMN Holding are engagend in the same business activities, under one holding company that oversees the companies. Through a holding company is considered to provide more economic benefits compared to a single company. The parent company's business activities will usually determine the type of business license that must be fulfilled by the parent company. One of the BUMN holding companies that becomes a financing institution in increasing added value in a sustainable manner for Micro, Small, Medium Enterprises and Cooperatives (UMKMK) which is based on the principles of good corporate governance (GCG) or good corporate governance. The method of research is normative legal research. Result of the research is during the Covid-19 pandemic, of course, extra funds were needed to meet the company's finances where subsudiaries experienced delays in making loans due to the Covid -19 pandemic, so subsidiaries needed to borrow funds from the holding company.